Investigations of cold cathode TPI1-10k/50 thyratron parameters at voltage up to 50 kV, current up to 10 kA, pulse duration of hundred nanoseconds - Akimov, A.V.; Bak, P.A.; Kazarezov, I.V.; Korepanov, A.A. (Вопросы атомной науки и техники, 2006)
The results of cold cathode TPI1-10k/50 thyratron parameters at voltage up to 50 kV, current up to 10 kA and pulse duration of hundred ns are described. The optimal parameters of thyratron power supply and pulse driver had been found. The jitter and thyratron own rise time as a function of load resistance has been find. The thyratron life time test data are cited.